Impact Assessment - Olszynski, Martin Z. (Environmental law and policy, 2020)
"Environmental Law and Policy, Fourth Edition examines environmental law across Canada, offering perspectives from each region and presenting samples of statutes, regulations, guidelines, cases, government policy, and academic writings. This casebook illustrates the links between environmental law and other related areas including science, politics, economics, and basic ethical and philosophical concerns."– Provided by publisher
OCLC: 1104965219